Investigating the Effectiveness of Cogniplus Cognitive Training Program on Social Cognition (Theory of Mind) in 6- to 8-year-old Children With Autism Spectrum Disorder - Zahra Tajik; Masoume Pourmohamadreza-Tajrishi; Marjan Posht Mashhadi; Razieh Bidhendi Yarandi (University of Social Welfare and Rehabilitation Sciences, 2024)
Objective Autism is one of the most common neurodevelopmental disorders. It causes problems in social cognition, communication, and understanding of self and others' feelings, and has a negative effect on the quality of a person's life. The present study determines the effectiveness of the Cogniplus cognitive training program on the social cognition (theory of mind (ToM) of children with autism spectrum disorder (ASD). Materials & Methods In a semi-experimental study with a pre-test, post-test design, and a control group with a two-month follow-up, 65 children (44 male and 21 female) from 6 to 11 years old with ASD were selected based on the convenience sampling method from individuals referred to one of autism rehabilitation centers in Shahr-e-Ray City, Iran. They were assessed by the autism spectrum screening questionnaire (ASSQ). Overall, 50 children (33 male and 17 female) with a score of 19 and above on the autism spectrum screening questionnaire were diagnosed with high-functioning autism. They entered into the study according to the inclusion criteria as follows: having speech ability, the absence of motor or intellectual disability, and visual and hearing impairments. Meanwhile, they were matched based on their age. They were randomly and equally assigned to two experimental and control groups. The parents completed the ToM test. The experimental group participated individually in 20 sessions (twice a week, 30 min per session), in the Cogniplus cognitive training program, but the control group only received mainstream services (occupational therapy, speech therapy, art therapy, and music therapy). The parents completed the ToM test in the last session and two months follow-up. The data were analyzed by the correlation analysis, analysis of regression, and generalized estimating equations in the SPSS software, version 27. Results The results of generalized estimating equations analysis showed that the Cogniplus cognitive training program improved social cognition (total, first level, and second level of ToM). Meanwhile, the β coefficient showed that 2.9, 3.08, and 0.96 of the variations, respectively, in the ToM levels as the first, the second, and the total, in children with ASD who received Cogniplus cognitive training program. Also, the variations lasted after a two-month follow-up. Conclusion Considering the positive effect of the Cogniplus cognitive training program on social cognition, the use of the Cogniplus cognitive training program can solve the need for therapists who have new cognitive insight into training. Also, the implementation of such programs can help to improve the social cognition of children with autism disorder with high functioning in real-life situations.